Three new species of Phyllodesmium Ehrenberg (Gastropoda: Nudibranchia: Aeolidoidea), and a revised phylogenetic analysis - Moore, Elizabeth; Gosliner, Terrence (Zootaxa, 2009)
Mimicry and camouflage are an important protective measure for nudibranch gastropods. In the genus Phyllodesmium, species have evolved elaborate morphological traits that allow them to be very cryptic among their coral prey. In this study, three new species of Phyllodesmium from the Philippine islands are described: Phyllodesmium tuberculatum n. sp., Phyllodesmium pinnatum n. sp., and Phyllodesmium karenae n. sp. The first two, P. tuberculatum and P. pinnatum, are highly cryptic on their prey and were already included in a phylogenetic analysis by Moore & Gosliner (in press). The third species (P. karenae) is newly discovered and has not yet been observed on its prey. A revised morphological phylogenetic analysis is presented that includes this species, as well as three species that were recently described by Burghardt et al. (2008a). In addition, the current analysis excludes a previously presumed new species, which was referred to as Phyllodesmium sp. 3 by Moore & Gosliner (in press), because it was determined to be an abnormally preserved specimen of P. jakobsenae. The newest species, P. karenae, has an unusual dental morphology, no branching of the digestive diverticula, and no zooxanthellae present in the cerata. It fell into the basal part of the phylogeny, as was expected based on previous general trends showing the derived status of symbiotic species. The three species described by Burghardt et al. (2008a), two of which are associated with xeniid corals, appear in a highly unresolved part of the phylogeny including other xeniid-associated species. One of these, P. koehleri, is not associated with xeniid corals but is indistinguishably intermixed within this clade. Decay analysis values for most nodes are low, indicating that support for this topology is lacking. It is recommended that the addition of less ambiguous characters, such as genetic sequences, be considered for further phylogenetic analyses.